Memory in the Middle Ages Approaches from Southwestern Europe. - Sabaté, Flocel (CARMEN monographs and studies., 2021)
Memory was vital to the functioning of the medieval world. People in medieval societies shared an identity based on commonly held memories. Religions, rulers, and even cities and nations justified their existence and their status through stories that guaranteed their deep and unbroken historical roots.The studies in this interdisciplinary collection explore how manifestations of memory can be used by historians as a prism through which to illuminate European medieval thought and value systems. The contributors draw the link between memory and medieval science, management of power, and remembra.